The Tyranny of Tools: The Politics of Knowledge Production in Gender Research - Cullen, B.; Lefore, N.; Debevec, L.; Snyder, K.A. (2024)
This chapter examines the trajectory of analytical frameworks and gender tools intended to understand and address the challenges and inequities that shape women’s engagement in agriculture. We argue that while a focus on tools in many agricultural development projects can help to identify barriers faced by women, it often does little to address the structural inequality in which women are embedded. We highlight the tendencies of tool-led gender analysis within agricultural projects to: (1) detach tools from their theoretical frameworks, (2) ignore the structural and socio-political obstacles to gender equality in specific contexts, and (3) view tools as silver bullets to address “gender problems” while primarily serving technical agendas. We argue that the co-option, sanitization and de-politicization of gender tools is partly the result of social scientists having to fit within institutional systems dominated by certain scientific logics, frameworks, disciplinary orientations, and social norms. We recommend that meaningful attempts to facilitate gender equality and women’s empowerment should be based on politically informed, contextualized understandings that are relevant to people’s lived realities, rather than concepts, tools, and data that are externally constructed and applied by outsiders to meet normative scientific, donor, and development agendas.